Catalytic Decomposition of HO on CoO Doped with AgO or ZnO - Gamil A. El-Shobaky; Abd. El-Mohsen M. Turky (Adsorption Science & Technology)
The effects of doping Co 3 O 4 with Ag 2 O (0.40–3.00 mol%) or ZnO (0.75–6.00 mol%) on the surface and catalytic properties of the solid were investigated via nitrogen adsorption at −196°C and the decomposition of H 2 O 2 at 30–50°C. Pure and doped samples were prepared by the thermal decomposition in air at 500–900°C of pure cobalt carbonate and carbonate samples treated with different proportions of silver or zinc nitrates. The results showed that Ag 2 O doping followed by precalcination at 500–900°C resulted in a significant decrease (ca. 25%) in the BET surface areas of the treated Co 3 O 4 samples. Treatment of Co 3 O 4 with ZnO followed by precalcination over the same temperature range effected a corresponding increase in the specific surface areas (ca. 28%). The addition of Ag 2 O to Co 3 O 4 effected a record increase in the corresponding catalytic activity towards the decomposition of H 2 O 2 . Thus, the maximum increase noted in the catalytic rate constant (k) measured at 30°C over Co 3 O 4 doped with 3.00 mol% Ag 2 O exhibited a 36-fold, 26-fold and 3.5-fold increase for catalysts precalcined at 500°C, 700°C and 900°C, respectively. Treatment of Co 3 O 4 with ZnO also effected an increase in the catalytic activity of the resulting solid. Thus, treatment of Co 3 O 4 with 6.00 mol% ZnO followed by precalcination at 500°C, 700°C and 900°C effected an increase of 109%, 28% and 36%, respectively, in the catalytic activity expressed in terms of the reaction rate constant measured at 30°C. The doping process did not modify the activation energy of the catalyzed reaction but increased the concentration of catalytically active constituents considerably without changing their energetic nature. Doping with Ag 2 O or ZnO led to an increase in the concentration of Co 3+ –Co 2+ ion pairs in the system and also generated corresponding Ag + –Co 2+ and Zn 2+ –Co 3+ ion pairs, thereby increasing the number of active constituents involved in the catalytic decomposition studied.